ISLAM DAN PLURALISME: KONSEP DAN STRATEGI IMPLEMENTASI DI PERSEKOLAHAN - kurnali sobandi (LPPM STAI Haji Agus Salim, 2023)
Islam is a holistic religion of public religion, and the closing religion that teaches divinity and humanity, including the problem of pluralism. The definition of pluralism in this case can be categorized in social pluralism and political pluralism.Social pluralism has meaning, historical trends, bases, mission, theory, and recognition of religions. Likewise, political pluralism has meaning, interpretation, action, concept, postulate, historical, and conditions in its implementation.Pluralism, in its form requires actualization from generation to generation so that the values ??and norms that exist in society and culture can be developed. Efforts to develop these values ??and norms in life and life occur in the education process.Pluralism education in schools requires clarity on the notion of pluralism education itself, it needs an effort to reorient Islamic religious education, and the approach to the implementation of education, as well as the pluralism education model in schooling.